Literature and the Senses - Kern-Stähler, Annette; Robertson, Elizabeth (Oxford University Press, 2023)
Literature and the Senses critically probes the role of literature in capturing and scrutinizing sensory perception. Organized around the five traditional senses, followed by a section on multisensoriality, the collection facilitates a dialogue between scholars working on literature written from the Middle Ages to the present day. The contributors engage with a variety of theorists from Maurice Merleau-Ponty to Michel Serres to Jean-Luc Nancy to foreground the distinctive means by which literary texts engage with, open up, or make uncertain dominant views of the nature of perception. Considering the ways in which literary texts intersect with and diverge from scientific, epistemological, and philosophical perspectives, these essays explore a wide variety of literary moments of sensation including the interspecies exchange of a look between a swan and a young Indigenous Australian girl; the sound of bees as captured in an early modern poem; the noxious smell of the 'Great Stink' that recurs in the Victorian novel; the taste of an aubergine registered in a poetic performance; tactile gestures in medieval romance; and the representation of a world in which the interdependence of human beings with the purple hibiscus plant is experienced through all five senses. The collection builds upon and breaks new ground in the field of sensory studies, focusing on what makes literature especially suitable to engaging with, contributing to, and challenging our perennial understandings of the senses.